Мультимодальні композиційні портландцементи з високою ранньою міцністю та модифіковані бетони на їх основі - Гев’юк, Ірина Миколаївна (Національний університет "Львівська політехніка", 2018)
Дисертаційна робота присвячена розробленню теоретичних основ технології композиційних портландцементів з високою ранньою міцністю типу CEM II/B-М (клінкер-фактор – 65%) за рахунок оптимізації речовинного та гранулометричного складів клінкеру та високодисперсних цементозаміщуючих матеріалів різного генезису з врахуванням особливостей розподілу розмірів частинок та їх поверхневої енергії, що забезпечує технічні, екологічні та економічні переваги даного типу композиційних портландцементів. Отримано комплекс експериментально-статистичних моделей технологічних і фізико-технічних показників четвертинних мультимодальних композиційних портландцементів з високою ранньою міцністю та модифікованих бетонів на їх основі, що кількісно характеризують комплексну синергетичну дію високодисперсних цементозаміщуючих матералів з бімодальною реакційно-хімічною поверхневою активністю та полікарбоксилатних суперпластифікаторів, досліджено будівельно-технічні властивості, здійснено промислове впровадження та розраховано техніко-економічну ефективність їх використання. Диссертация посвящена разработке теоретических основ технологии композиционных портландцементов с высокой ранней прочностью типа CEM II/B-М (клинкер-фактор - 65%) за счет оптимизации вещественного и гранулометрического составов клинкера и высокодисперсных цементозамещающих материалов различного генезиса с учетом особенностей распределения размеров частиц и их поверхностной энергии, что обеспечивает технические, экологические и экономические преимущества данного типа композиционных портландцементов. Получено комплекс экспериментально-статистических моделей технологических и физико-технических показателей четвертичных мультимодальных композиционных портландцементов с высокой ранней прочностью и модифицированных бетонов на их основе, количественно характеризующих комплексное синергетическое взаимодействие высокодисперсных цементозамещающих матералов с бимодальной реакционно-химической поверхностной активностью и поликарбоксилатных суперпластификаторов, исследованы строительно-технические характеристики, осуществлено промышленное внедрение и рассчитана технико-экономическая эффективность их использования. The dissertation is devoted to the development of theoretical bases of multimodal Portland cement technology with high early strength of CEM II/B-M type (clinker-factor 65%) due to optimization of the main constituents and granulometric composition of clinker and supplementary cementitious materials of different genesis taking into account the particle size distribution and their surface energy, which provides the technical, ecological and economic benefits of this type of Portland composite cement. An analytical review of literary sources devoted to the problems of obtaining of concrete with improved operational characteristics was made, issues related to the principles of modification of cementing systems were considered, as well as theoretical preconditions of the research were determined. The characteristics of the materials and the main methods of research used in the work are described. The results of development and research of multimodal composite Рortland cement with high early strength are presented. Complex estimation of dispersion of mineral components, based on determination of specific surface, granulometric composition of particles and magnitude of their interfacial surface is carried out. The complex of experimental and statistical models of technological and physical and technical parameters of quaternary multimodal composite Рortland cements with high early strength, quantitative characterizing the complex synergetic effect of highly dispersed cementitious substrates with bimodal reactive-chemical surface activity in the mechanism of growth of their early and standard strength are obtained. It is shown that the combination of the main constituents of different genesis provides optimization of properties (workability, standard and early strength, durability, cost, environmental impact) of a quaternary multimodal composite Рortland cement with high early strength of CEM II/B-M 42.5R type. The compositions of modified concretes based on multimodal Portland composite cements have been developed and their construction and technical properties have been investigated. It is shown that modified concretes of classes C20/25...С32/40 by the estimating specific strength fcm2/fcm28 =0,32...0,35 are characterized by average strength increase. The complex modifier with acceleration action Glenium ACE 430 + Pozzolit 501 provides the production of rapid-hardening concretes (fsm2=31,5 MPa, fcm2/fcm28 = 0,58), which are also characterized by accelerated hardening at frost. Industrial batches of Quaternary Portland composite cements of CEM II/B-M (S-P-L) type were produced. Pilot batch of multimodal Portland composite cement with high early strength DSTU B EN 197-1 - CEM II/B-M (S-P-L) 42.5R-LH has been produced on the basis of separate milling technology in the quantity of 600 t. At release of commercial concrete at the Subsidiary Enterprise "Spetszalizobeton" PJSC “Ivano-Frankivsk Cement”, the efficiency from the implementation of development, taking into account the cost of production, is 75 ... 100 UAH per 1 m3 of concrete.
Мультимодальные композиционные портландцементы с высокой ранней прочностью и модифицированные бетоны на их основе
Multimodal Portland-composite cements with high early strength and modified concretes on their basis
Keywords: четвертинний мультимодальний композиційний портландцемент з високою ранньою міцністю; цементозаміщуючі матеріали; поверхнева активність; модифікований бетон; будівельно-технічні властивості; четвертичный мультимодальный композиционный портландцемент с высокой ранней прочностью; цементозамещающие материалы; поверхностная активность; модифицированный бетон; строительно-технические свойства; Quaternary multimodal Portland composite cement with high early strength; supplementary cementitious materials; surface activity; modified concrete; constructional and technical properties; 666.942.32:666.9.035